Dilema Yuridis Kewenangan Penuntutan Tindak Pidana Militer: Konstruksi Konflik Norma dan Urgensi Peran Jampidmil - Adhi Akbar Idianto; HS Tisnanta; Rini Fathonah; Heni Siswanto; Muhtadi (Jurnal Hukum Lex Generalis, 2026)
The dualism of prosecution authority between the Attorney General's Office and the Military Oditurat creates a conflict of norms within the Indonesian criminal justice system. This normative legal research employs statutory and conceptual approaches to examine the construction of this conflict of norms and the urgency of the role of the Junior Attorney General for Military Crimes (Jampidmil). The findings indicate a contradiction between the single prosecution system principle adopted by the Law on the Attorney General's Office and the exclusive prosecution authority of the Oditurat based on the Law on Military Courts. This conflict impacts legal uncertainty and the fragmentation of law enforcement. Jampidmil serves as an instrument for coordination and harmonization; however, it has not been able to substantively eliminate the dualism of prosecution authority. Therefore, strengthening regulatory harmonization is required to ensure legal certainty in the prosecution practice of military criminal cases.